Can Flipped Learning Drive Higher-Order Thinking in Sustainable Education? A Systematic Literature Review - Rahayuningsih, Retno; Hartono, Rudi; Pratama, Hendi (Universitas Hamzanwadi, 2025)
Rapid global change and the demands of 21st-century education have created an urgent need to develop students’ higher-order thinking skills (HOTS), critical, creative, and problem-solving abilities, yet evidence on how flipped learning (FL) supports these skills remains fragmented. This systematic literature review addresses that gap by synthesizing recent studies (2021–2025) on the impact of FL on HOTS across formal education levels and diverse cultural contexts, with particular attention to implications for sustainable education. Following PRISMA guidelines, 32 peer-reviewed empirical studies were identified from Scopus, ERIC, and ProQuest using predefined inclusion and exclusion criteria. Methodological quality was appraised using a simplified CASP checklist, and inductive thematic synthesis was employed to identify patterns in pedagogy, technology use, and HOTS outcomes. Findings indicate that FL can enhance cognitive engagement, learner autonomy, and performance when integrated with inquiry-based and collaborative strategies; critical thinking often improved through structured argumentation, creativity through project-based and digital tasks, and problem-solving through real-world, team-based learning. However, effects varied by discipline, education level, and contextual factors such as digital readiness and instructional design quality; several studies reported minimal gains in low-tech or weakly scaffolded settings. These results underscore FL’s potential as a sustainable pedagogical framework that optimizes resources and fosters lifelong learning, but also highlight gaps: most studies were small-scale, quasi-experimental, and lacked longitudinal or cross-cultural comparison. Future research should adopt more rigorous, context-sensitive designs and explore how FL compares with other active learning models to inform curriculum and teacher training policies.